Glammix / Mehmet Zaidell Kamarudzaman … [et al.] - Kamarudzaman, Mehmet Zaidell; Mohamad Fauzi, Farah Wahedah; Ishak, Farrah Asyikin; Kamarudin, Irdina; Muhabir, Maryam Nabihah; Ibrahim, Lina Mazwein (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Choosing daily outfits can be a time-consuming and frustrating task, often leading to decision fatigue and wasted mental energy. This daily struggle transcends age, gender, and profession. Traditional wardrobe management methods, like overflowing closets and mental checklists, lack efficiency and often result in outfit combinations that fail to capitalize on existing clothing items. Glammix is a mobile application that facilitates the outfit selection process. Glammix aims to empower users to make quick and confident clothing choices by providing personalized outfit recommendations based on their wardrobe, weather conditions, and occasion. Glammix utilizes AI algorithms to analyze user preferences, clothing styles, and fit. This personalized approach sets it apart from existing wardrobe management apps that offer generic outfit suggestions or focus solely on cataloging clothes. By reducing decision fatigue and streamlining the dressing process, Glammix helps users save time and mental energy. It can also promote sustainable fashion by encouraging the utilization of existing clothing items and minimizing impulse purchases. This translates to a more mindful approach to fashion consumption.